Research productivity of teacher educators in a Philippine state university - Amanonce, Jay-cen T.; Temporal, Conchita M.; Vecaldo, Rudolf T.; Calubaquib, Jhoanna B.; Tamayao, Antonio I.; Malana, Maribel F.; Tamayo, Ria A.; Calanoga, Marie Claudette M. (Intelektual Pustaka Media Utama, 2025)
Research productivity in higher education institutions (HEIs) is essential for university rankings and quality assurance. However, studies show that Filipino researchers, particularly in HEIs, have low research output. This quantitative study focuses on the research productivity of 100 teacher educators at a Philippine state university, analyzing it in relation to their professional characteristics. The results reveal generally low research productivity, especially in externally funded projects, research utilization, citations, awards, and intellectual property registrations. Significant differences in research productivity were found based on years of service, educational attainment, faculty rank, research teaching experience, and seminar participation. Teacher educators with more years of service, advanced academic degrees, higher academic ranks, research teaching experience, and greater seminar attendance tend to have higher research productivity. To improve research output, institutions should prioritize faculty professional development.